The origins of the universe: why is there something rather than nothing?. Issue 1 (14th September 2015) - Paulson, Steve; Albert, David; Holt, Jim; Turok, Neil
Abstract : Perhaps the greatest mystery is why the universe exists in the first place. How is it possible for something to emerge from nothing, or has a universe in some form always existed? This question of origins—both of the universe as a whole and of the fundamental laws of physics—raises profound scientific, philosophical, and religious questions, culminating in the most basic existential question of all: Why are we here? Discussion of this and related questions is presented in this paper.